Etude comparative de la qualité sanitaire de deux types du lait (chèvre, brebis) - Haitous, Mohamed (My University, 2021)
Milk has been a very important part of the diet from time immemorial, both for humans and animals. Two (02) milk samples were collected from two different animals (goat and sheep) from the wilaya of Tiaret.The objective of this work is to assess the quality of raw sheep's milk and goat's milk from the wilaya of Tiaret. The physicochemical quality of milk is evaluated by measuring the pH, the reductase test, the acidity. The microbiological examination involved the enumeration of FAMT, total and fecal coliforms, Staphylococcus aureus, fecal streptococci and salmonella. The results of the physicochemical analyzes show that the pH (6.57 - 7.85) and the acidity at (21.62-22.8). And The results of the enumeration are; FAMT (2.9 × 104), CT (1.03 × 103), CF (3.9 × 10) and streptococci (3.93 × 102). We recorded the presence of staphylococci in 40% of the samples and a total absence of salmonella. Our results indicate that sheep's milk and goat's milk from the Tiaret region average microbiological quality.
Keywords: sheep, goat, physicochemical quality, staphylococci, salmonella